2009
DOI: 10.1212/01.wnl.0000340982.01727.6e
|View full text |Cite|
|
Sign up to set email alerts
|

High-resolution diffusion tensor imaging in the substantia nigra of de novo Parkinson disease

Abstract: Background:In the midbrain of patients with Parkinson disease (PD), there is a selective loss of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
308
8
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(363 citation statements)
references
References 27 publications
41
308
8
6
Order By: Relevance
“…Seven of 9 studies included patients taking antiparkinsonian medications, medication details were unavailable for one, 6 and the final study 13 included only medicationnaive patients. The study on early, medication-naive patients 13 found on post hoc analysis that the caudal region of the SN had sensitivity and specificity of 100% for differentiating patients with PD from controls. This study, along with another, 24 did not find an association between disease severity and FA in SN.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven of 9 studies included patients taking antiparkinsonian medications, medication details were unavailable for one, 6 and the final study 13 included only medicationnaive patients. The study on early, medication-naive patients 13 found on post hoc analysis that the caudal region of the SN had sensitivity and specificity of 100% for differentiating patients with PD from controls. This study, along with another, 24 did not find an association between disease severity and FA in SN.…”
Section: Resultsmentioning
confidence: 99%
“…It is not known, however, if these techniques can robustly identify patients with PD, a necessity for translation into a viable biomarker, and conclusions on diagnostic accuracy cannot be drawn from our meta-analysis results. Tantalizingly, post hoc receiver operator characteristic analysis in the caudal SN in one small, early-stage study 13 of nonmedicated patients showed 100% sensitivity and specificity for distinguishing patients with PD from healthy controls. Such work, however, remains experimental and requires replication.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, some investigators have applied diffusion tensor imaging and demonstrated reduced fractional (FA) in the region thought to correspond to ascending nigrostriatal fibers [2], although this finding has not yet been reproduced. One group has demonstrated reduced FA in the substantia nigra itself, with outstanding sensitivity and specificity in caudal regions [3], while others have suggested that FA may be reduced in other regions [4,5], perhaps representing alterations in white matter integrity or in functional connectivity. Yet another group has suggested that diffusion tensor imaging measures of nigrothalamic connectivity combined with a modified T1 nigral volumetric study have improved sensitivity and specificity for PD [6].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…The most common finding in many DTI studies was a reduction in fractional anisotropy (FA) in the substantia nigra of PD patients (Chan et al, 2007;Du et al, 2011;Peran et al, 2010;Vaillancourt et al, 2009;Yoshikawa, Nakata, Yamada, & Nakagawa, 2004), and the reduction in FA values in the substantia nigra was inversely correlated with the severity of the clinical symptoms of PD patient (Chan et al, 2007). Extranigral WM changes have been observed in PD patients.…”
Section: Structural Connectivitymentioning
confidence: 99%